Clinic and Emergency Room Evaluation and Testing of Headache. Issue 9 (30th September 2015) - Nye, Barbara L.; Ward, Thomas N.
<x xml:space="preserve">Abstract</x> Background Evaluation of the headache patient in the outpatient clinic and emergency department (ED) has different focuses and goals. The focus of this paper is to review the evaluation of patients in both settings with mention of evaluation in the pediatric and pregnant patient population. The patient's history should drive the practitioner's decision and evaluation choices. We review recommendations made by the American Board of Internal Medicine and American Headache Society through the Choosing Wisely Campaign, which has an emphasis on choosing the right imaging modality for the clinical situation and elimination/prevention of medication overuse headache, as well as the US Headache Consortium guidelines for migraine headache. We will also review focusing on ED evaluation of the pediatric patient and pregnant patient presenting with headache. Conclusion At the end of the review we hope to have provided you with a framework to think about the headache patient and what is the appropriate test in the given clinical setting in order to ensure that the patient gets the right diagnosis and is set on a path to the appropriate management plan.